ASSESSMENT OF PLATELET CONCENTRATE PREPARED FROM FRESH AND OVERNIGHT HELD WHOLE BLOOD - Abu Kasim, Halimahtun Sa'adiah; Al-hassan, Faisal Muti; Lim, Vuanghao (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Separation of platelet rich plasma (PRP) within 8 hours after holding whole blood at ambient temperature is the current practice in the preparation of platelet concentrate (PC). However, the ability to hold whole blood for up to 24 hours prior to PC preparation would allow every unit of whole blood to be used regardless of the distance from the collection site to the processing centre. Therefore the aim of this study is to assess and compare the platelet quality and activation of the platelet concentrate prepared from fresh whole blood (within 8 hours from collection) and overnight hold of whole blood at room temperature. In this study, 23 units of PC were prepared freshly from whole blood (i.e., within 8 hours of collection) and another 23 units were prepared after 24 hours of storage at 20–24 ºC. The following parameters of each unit of PC were assessed: pH, total white blood cell (TWBC) count, platelet count, presence of swirling, and platelet activation. When the parameters were compared between groups, no significant difference in platelet activation rate was found on sampling days 1, 3, and 5. pH and TWBC count for both groups were within the quality requirements of the National Blood Centre (> 75% units tested fall within the standard), but not all of the samples complied with the standard requirement for platelet count. All units of PC prepared after 24 hours showed the presence of swirling, whereas one unit of PC in the fresh group did not show swirling activity after 3 days of storage. Delaying whole blood processing for up to 24 hours does not significantly affect certain in vitro quality or activation parameters as compared with freshly prepared PC.